P2-S1.07 Sadness, poor school work, running away, and sexual risk behaviour among urban female African American adolescents. (10th July 2011) - Safran, M; Tian, L Hui; Hogben, M; Braxton, J; Robitz, R; Koumans, E
Abstract : Background: Correlations between delinquency, poor school performance, and poor sense of emotional well-being among adolescents are often recognised, but their correlation with risky sexual behaviour has not been as well explored, particularly in African American female populations. Methods: We surveyed 743 sexually active females, age 13 to 19 (mean 16.6 years), attending a predominantly African American urban adolescent clinic. We asked about sexual activity and about poor school work, delinquency (running away from home), poor emotional well-being (feeling unhappy, sad, or depressed), and receiving counselling. To assess associations, ORs were calculated with 95% CIs. A respondent was classified as having correct and consistent condom use if her responses indicated that, during the past 90 days ALL of the following were true: she had engaged in vaginal sexual intercourse at least once, a condom had been used during all vaginal sexual intercourse, the condom was always put on prior to genital contact and remained on throughout sexual intercourse, a condom had never broken while being worn, and a condom had never been put on inside out and then flipped over and put back on again. Results: Approximately 10% of females had 0 sexual partners in the past 90 days, 54% had 1 partner, and 36% had 2 or more partners. Those responding true to whether they felt unhappy, sad, or depressed in the past 6 months (12% of the sample) were more likely to report more than one sexual partner compared to those responding "not true", OR=2.13 (95% CI 1.33—to 3.39), and less likely to report correct and consistent condom use, OR=0.45 (95% CI 0.22—to 0.91) (Abstract P2-S1.07 table 1 ). Those who reported seeing a counsellor for emotional problems (13% of the sample) were more likely to report multiple partners, OR=1.75 (95% CI 1.11—to 2.74) and less likely to report correct and consistent condom use, OR=0.31 (95% CI 0.12—to 0.78) than those who reported no such counselling. Poor school performance and running away from home were associated with having more than one partner, but generally not with inconsistent or incorrect condom use. (Abstract P2-S1.07 table 1 ). Conclusion: Our results highlight the importance of mental health and sexual behaviour assessments in adolescent healthcare settings. Further research is needed to assess whether counselling and improved emotional well-being can reduce sexual behaviours that place adolescents at risk.